Maternal nutritional manipulations program adipose tissue dysfunction in offspring - Lecoutre, Simon; Breton, Christophe (Frontiers in Physiology, 2015)
Based on the concept of Developmental Origin of Health and Disease, both human and animal studies have demonstrated a close link between nutrient supply perturbations in the fetus or neonate (i.e., maternal undernutrition, obesity, gestational diabetes and/or rapid catch-up growth) and increased risk of adult-onset obesity. Indeed, the adipose tissue has been recognized as a key target of developmental programming in a sex-and depot-specific manner. Despite different developmental time windows, similar mechanisms of adipose tissue programming have been described in rodents and in bigger mammals (sheep, primates). Maternal nutritional manipulations reprogram offspring’s adipose tissue resulting in series of alterations: enhanced adipogenesis and lipogenesis, impaired sympathetic activity with reduced noradrenergic innervations and thermogenesis as well as low-grade inflammation. These changes affect adipose tissue development, distribution and composition predisposing offspring to fat accumulation. Modifications of hormonal tissue sensitivity (i.e., leptin, insulin, glucocorticoids) and/or epigenetic mechanisms leading to persistent changes in gene expression may account for long-lasting programming across generations.